Usefulness of upper gastrointestinal endoscopy in children - Bahubali D Gadgade; Venkatesh M Annigeri; Anil Halageri; Praveen Bagalkot (Wolters Kluwer Medknow Publications, 2018)
Context: Upper gastrointestinal (GI) endoscopy is now important investigation in children. Although endoscopy is used routinely by pediatric surgeons, there are no recent Indian studies which have evaluated endoscopy within a Department of Pediatric Surgery. Aims: It was done with the aim to define the diagnostic value of upper GI endoscopy and evaluate the outcome. Subjects and Methods: This is a descriptive retrospective study. Cases <14 years between January 2013 and October 2016 were included. An Olympus GIF-Q150 video gastroscope was used for all procedures. This study was approved by the institute research and ethical committee, and patient confidentiality was maintained using unique identifiers. The data were analyzed using Microsoft Excel 2010 and SPSS (Version 19) software. Results: The most common indication for endoscopy was for hematemesis (25.3%, n = 18) followed by foreign body removal (22.5%, n = 16). There were 18 normal cases. Foreign body removal was done in 18 cases. Among esophageal varices, banding was done in seven cases and dilatation of stricture was done in eight cases. Conclusion: Upper GI endoscopy is significantly associated with positive organic finding and so it is a valuable and essential diagnostic procedure.